Body burden of pesticides and wastewater-derived pollutants on freshwater invertebrates: Method development and application in the Danube River. (July 2016) - Inostroza, Pedro A.; Wicht, Anna-Jorina; Huber, Thomas; Nagy, Claudia; Brack, Werner; Krauss, Martin
Abstract: While environmental risk assessment is typically based on toxicant concentrations in water and/or sediment, awareness is increasing that internal concentrations or body burdens are the key to understand adverse effects in organisms. In order to link environmental micropollutants as causes of observed effects, there is an increasing demand for methods to analyse these chemicals in organisms. Here, a multi-target screening method based on pulverised liquid extraction (PuLE) and a modified QuEChERS approach with an additional hexane phase was developed. It is capable to extract and quantify organic micropollutants of diverse chemical classes in freshwater invertebrates. The method was tested on gammarids from the Danube River (within the Joint Danube Survey 3) and target compounds were analysed by liquid chromatography-tandem mass spectrometry (LC-MS/MS). Furthermore, a non-target screening using high resolution-tandem mass spectrometry (LC-HRMS/MS) was conducted. A total of 17 pollutants were detected and/or quantified in gammarids at low concentrations. Pesticide concentrations ranged from 0.1 to 6.52 ng g −1 (wet weight), those of wastewater-derived pollutants from 0.1 to 2.83 ng g −1 (wet weight). The presence of wastewater-derived pollutants was prominent at all spots sampled. Using non-target screening, we could successfully identify several chlorinated compounds. These results demonstrate for the first time the presence of pesticides and wastewater-derived pollutants in invertebrates of the Danube River. Graphical abstract: Highlights: A method based on pulverised liquid extraction/QuEChERS for organic micropollutants in invertebrates was developed. The method is applicable in assessing target environmental pollutants in invertebrates by LC-MS/MS. The method allows for a nontarget screening of extracts by LC-HRMS. First body burden analysis of pesticides and wastewater-derived pollutants in invertebrates in the Danube River is reported. Abstract : Capsule: A multi-target screening method was developed to quantify the internal concentration of micropollutants in a freshwater macroinvertebrate population.